An Analysis of the Public Relations Approach adopted in Obafemi Awolowo University and University of Lagos to handle Sex-for-Grades Situations - Amadi, Richard Nlemenya; Umor, Ebenezer Francis (NIU Journal of Social Sciences, 2020)
Public Relations has become generally accepted as an important element of business, government and all aspect of everyday life. Being that it is a deliberate, planned, and sustained effort to establish and maintain mutual understanding between an organisation and its publics, its approach to the sex for grade situation in the Obafemi Awolowo University and University of Lagos justify the importance of the practice to any organisation. With the excellence and systems theories as the theoretical framework, the study qualitatively assessed and analysed the press releases from the universities cum in-depth interviews with the public relations heads of both institutions. The findings shows that the universities carried out some public relations activities proactively that could have avoided the scandal such as issuance of press releases that informed the publics of the authorities zero tolerance for the unwholesome practice of sex-for-grades. The study among others recommends that heads of public relations of higher institutions be made part of management of the universities to enable for full public relations activities and practice to ensure the image and reputation of the tertiary institutions are properly handled. Keywords: Public Relations, Ivory Towers, Approach, Sex-for-grades, Publics, Scandal etc.